2020
DOI: 10.1007/s43390-020-00088-3
|View full text |Cite
|
Sign up to set email alerts
|

Intermediate-term annualized curve progression of adolescent idiopathic scoliosis curves measuring 40° or greater

Abstract: Study design Prospective cohort study.Objectives The objective of this study was to examine intermediate-term progression for a large series of patients with adolescent idiopathic scoliosis (AIS) with curves 40° or greater. Background Curve progression in AIS has been well documented for smaller curves in adolescence up to skeletal maturity; however, the data on curve progression past 40° or into adulthood are limited. With many surgeons recommending surgical correction when patients reach this threshold, it i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 13 publications
0
11
0
Order By: Relevance
“…Several studies analysed an ACP defining the growth of the Cobb angle over one year. In a prospective cohort study, Ward et al [35] found ACP was not linear over time in curves > 40° Cobb angles in 738 patients. Mean ACP was 6.3 ± 10.4°, yet, in the first year of follow-up, ACP was 11.5.…”
Section: Annual Curve Progression (Acp)mentioning
confidence: 97%
“…Several studies analysed an ACP defining the growth of the Cobb angle over one year. In a prospective cohort study, Ward et al [35] found ACP was not linear over time in curves > 40° Cobb angles in 738 patients. Mean ACP was 6.3 ± 10.4°, yet, in the first year of follow-up, ACP was 11.5.…”
Section: Annual Curve Progression (Acp)mentioning
confidence: 97%
“…Although a main study objective was to identify patients requiring surgery via determinants of progression during early adulthood, we were unable to account for "late" progression extending beyond the average 12-year observational period. We also assumed a linear rate of Cobb angle change, but there are reports to the contrary among large untreated curves 31 .…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…Bracing is recommended for curves between 25−45 degrees, and surgery is considered for angles at or above 45 degrees. 2 In the absence of treatment, curvature is estimated to increase at a rate of 1% per year, although growth and vulnerability greatly accelerate curve increase in some adolescents, 3,4 and authors disagree about the natural history. 3,4…”
Section: Introductionmentioning
confidence: 99%
“…2 In the absence of treatment, curvature is estimated to increase at a rate of 1% per year, although growth and vulnerability greatly accelerate curve increase in some adolescents, 3,4 and authors disagree about the natural history. 3,4…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation